(untitled) (Ozone Therapy Global Journal, 2021)
The use of ozonized oils in medicine has recently gain importance, because it’s recognized antimicrobial potential and the most frequent spread of microorganisms that are resistant to conventional antimicrobial agents. This paper reviews the general and main clinical applications of ozonated oils that have appeared in scientific literature between 1859-2020. The compound derived from the reaction of ozone with fatty acids and other substrates can acts as a germicide, immune stimulant and tissue restoration agent. The biological activities and stability of the ozonated oils allows the development of standard formulations that deliver the benefits of ozone, supported by pre-clinical and clinical studies. The quality of the ozonized oil should be of paramount importance for its use in clinic in order to guaranty its efficacy and avoid toxicity. Chemical and physical characterization and a precise peroxide values (as index of dosage) will be considering as a quality criterium of one medicinal ozonized oil preparation. Today the main applications of the ozonized oil are for external use essentially in dermatology, dental, ophthalmology and gynaecology, however there are evidences of immune-stimulating, germicide and repair effects when used orally. Additional clinical trials are need in order to support the clinical used of ozonized oils, but bases in standardized and stable formulations